Representasi Keresahan Mahmoud Darwish dalam Puisi al-Sijn: Kajian Semiotik Riffaterre - Mukhotob Hamzah; Muhammad Barrunnawa (Al-Ma‘rifah, 2021)
Anchored in the characteristic of a poem having a meaning beyond the sentence, this study aims to reveal the meaning of a poem entitled al-Sijn written by Mahmoud Darwish. Darwish is called to people around the world as the revolutionary poet because of his maneuvers against Israel over its occupation of Palestina. Employing descriptive analysis, Riffaterre’s Semiotic theory is used as the framework involving four basic components namely indirectness of expressions, heuristic and hermeneutic readings, matrices, and models, variants, and hypograms as parameters in collecting and analyzing the data. The findings of this study indicate that poem al-Sijn is the expression of a poet’s emotion feeling a sense of alienation from his place. It involves expression on the consumed foods, identity as a Palestinian, and his hopes to have freedom and independence. Further, through the lens of hypogram analysis, a similar poem is entitled Barqiyah min al-Sijn because it implies the same meanings as al-Sijn and is related to each other.